If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(x + -3) = 4x + -1b Reorder the terms: a(-3 + x) = 4x + -1b (-3 * a + x * a) = 4x + -1b (-3a + ax) = 4x + -1b Reorder the terms: -3a + ax = -1b + 4x Solving -3a + ax = -1b + 4x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Reorder the terms: -3a + ax + b + -4x = -1b + b + 4x + -4x Combine like terms: -1b + b = 0 -3a + ax + b + -4x = 0 + 4x + -4x -3a + ax + b + -4x = 4x + -4x Combine like terms: 4x + -4x = 0 -3a + ax + b + -4x = 0 The solution to this equation could not be determined.
| x/5-2=7 | | W/10+18=21 | | (8)(-4)= | | 2=s/3-2 | | 15/16A=-8/25 | | 45=s+33 | | 6(4x-8)=2(12x+9) | | 10-(-82)= | | 20/v=5 | | 106=30+g | | -47-(-9)= | | 16x-5=30+11x | | 34=j-39 | | 5x+8=10x | | 157=66+q | | -6y=-2x-12 | | d-16=47 | | x^2+x=135 | | x^2+31y=173 | | -26-76= | | -(8y+1)-(-7y-2)=-1 | | 87=a+48 | | f+6=87 | | -5(-9z+1)=2(8+7z) | | 54=82-y | | 25-b=15 | | c+15=76 | | c+15=76 | | x=18+2x | | 4=s/9 | | 57-t=49 | | (x+2)/3-4x=8 |